PREDICTIVE ANALYTICS OF THE FRAUD PREVENTION AND DETECTION AT ASF LEVEL - Constanta Iacob; Ersilia Catrina (Annals of the University of Craiova: Economic Sciences Series, 2016)
A need for greater rigor, which is felt by insurance companies in order to guarantee the fundamental balance of their financial sources, led to intensification of the concerns for preventing and combating fraud. The scope of the controller's mission is variable and its limits are set by the control program which has been established. In assessing the fair price of the caused damage, the essential role of the controller is to put a stop to the fraud and to avoidearly damage coverage.But information is required in order to accomplish this.The predictive analytics, of those processes necessary to prevent and combat fraud, is a way of passing from a retroactive and intuitive process to a proactive one, that is oriented according to the information possessed. Based on this approach, insurance companies can build models, to predict the risk of fraud, in order to reduce their financial-cost impact.